2017
DOI: 10.5853/jos.2016.02061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Spot Sign, Blend Sign and Black Hole Sign for Outcome Prediction in Patients with Intracerebral Hemorrhage

Abstract: Background and Purpose Blend sign (BS) and black hole sign (BHS) on non-contrast computed tomography (NCCT) and spot sign (SS) on CT-angiography (CTA) are indicators of early hematoma expansion in spontaneous intracerebral hemorrhage (ICH). However, their independent contributions to outcome have not been well explored. Methods In this retrospective study, inclusion criteria were: 1) spontaneous ICH and 2) NCCT and CTA performed on admission within 6 hours after onset of symptoms. Discharge outcome was dichoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 13 publications
2
52
1
Order By: Relevance
“…Early CT protocols in patients with ICH used only NCCT or CTA after NCCT for evaluation of critical imaging findings of ICH expansion [19]. Subsequent papers reported the relationship between imaging findings of CTA and NCCT and ICH expansion [20][21][22]. The study of Sporns et al [20] found that NCCT imaging markers were strongly correlated with an established spot sign.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early CT protocols in patients with ICH used only NCCT or CTA after NCCT for evaluation of critical imaging findings of ICH expansion [19]. Subsequent papers reported the relationship between imaging findings of CTA and NCCT and ICH expansion [20][21][22]. The study of Sporns et al [20] found that NCCT imaging markers were strongly correlated with an established spot sign.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that a spot sign has a higher sensitivity for outcome prediction than does a black hole sign or blend sign alone, both NCCT and CTA should be acquired if possible [20]. The results of other studies [21] have suggested that CT variables indicating early hematoma expansion, such as spot sign on CTA, are the most reliable predictors of outcome. Also, a spot sign had a higher sensitivity for predicting outcome than did black hole sign in any location (34.6% vs. 23.1%) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Of the blend sign, spot sign and black hole sign, the spot sign was the most reliable outcome predictor. (35) Barras CD et al (36) have reported that heterogeneity of density within the haematoma independently predicted poor outcome. These signs however are not present in all patients and hence cannot be applied to all patients with uniformity.…”
Section: Discussionmentioning
confidence: 99%
“…The black hole sign is a relatively hypodense area within a hyperdense hematoma, with an obvious boundary adjacent to brain tissue (5). The blend sign and the black hole sign on NCCT are associated with the spot sign on CTA, and all three are predictive factors for a poor outcome in patients with sICH (11). However, no studies have compared the predictive value of the blend sign and the black hole sign on NCCT in the same cohort of patients with sICH.…”
Section: Discussionmentioning
confidence: 99%